1998
DOI: 10.1002/1529-0131(199801)41:1<26::aid-art4>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Association between strong inflammatory response and low risk of developing visual loss and other cranial ischemic complications in giant cell (temporal) arteritis

Abstract: The presence of a strong acute-phase response defines a subgroup of patients at very low risk of developing cranial ischemic complications. Our findings provide a rationale for testing less aggressive treatment schedules in these individuals. Conversely, a low inflammatory response and the presence of transient cranial ischemic events provide a high risk of developing irreversible ischemic complications and require a prompt therapeutic intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
60
1
1

Year Published

1998
1998
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 229 publications
(70 citation statements)
references
References 44 publications
7
60
1
1
Order By: Relevance
“…In 2000, Weyand et al emphasized that interleukin (IL)-6 may act as a biological marker of GCA activity in untreated and treated GCA patients [19]. Cid et al reported that presence of a strong acute phase response defined a subgroup of patients with very low risk of developing visual loss and cranial ischemic complications in GCA [20]. In line with this report, Hocevar et al confirmed the negative association between high levels of acute phase proteins and visual loss and exposed a novel positive association between acute phase proteins and relapse in GCA patients [5].…”
Section: Introductionsupporting
confidence: 87%
“…In 2000, Weyand et al emphasized that interleukin (IL)-6 may act as a biological marker of GCA activity in untreated and treated GCA patients [19]. Cid et al reported that presence of a strong acute phase response defined a subgroup of patients with very low risk of developing visual loss and cranial ischemic complications in GCA [20]. In line with this report, Hocevar et al confirmed the negative association between high levels of acute phase proteins and visual loss and exposed a novel positive association between acute phase proteins and relapse in GCA patients [5].…”
Section: Introductionsupporting
confidence: 87%
“…Clinical findings of the study group (table 1) were similar to previously published series except for a higher frequency of ischaemic complications, which served well the purpose of this study 10 12 13 14. Twenty-six out of these 61 patients developed GCA-related ischaemic complications.…”
Section: Methodssupporting
confidence: 85%
“…Visual impairment is the most common ischaemic complication in GCA and has a deep impact on patients’ quality of life 10 11 12 13 14 15 16. Scarce necropsy studies focusing on the anatomical substrate of AION have shown that posterior ciliary and cilioretinal arteries supplying the optic nerve and retina may be involved by GCA lesions17 18 19 Irreversible visual loss is often preceded by recurrent episodes of transient blindness (amaurosis fugax), a medical emergency highly predictive of subsequent permanent visual defects in most series 10 11 12 13 14 15. The transient and often repetitive nature of amaurosis fugax suggests the contribution of inflammation-induced vasospastic phenomena in the pathogenesis of ischaemic complications.…”
mentioning
confidence: 99%
“…However, in the modern era, these symptoms are less common,22 but the inflammatory markers are usually abnormal prior to treatment, including erythrocyte sedimentation rate (ESR), C reactive protein (CRP) and/or plasma viscosity (PV). These blood tests are useful in supporting a diagnosis of GCA, but are less useful for monitoring disease activity, because they are suppressed by glucocorticoids.…”
Section: Gca and Pmr: Two Diseases Or One?mentioning
confidence: 99%
“…Factors that predispose to permanent visual loss or stroke are older age and previous ischaemic features. Patients who have already suffered transient visual loss or transient cerebral ischaemic events by the time of diagnosis of GCA are more likely to present with permanent visual loss or stroke 22 37 38. Ischaemic complications during glucocorticoid treatment are also more likely to occur in those who presented with ischaemic features pretreatment 37 39.…”
Section: Gca and Pmr: Two Diseases Or One?mentioning
confidence: 99%